Following coherent multichannel nuclear wave packets in pump-probe studies of O2 with ultrashort laser pulses - Xue, Shan; Du, Hongchuan; Hu, Bitao; Lin, C. D.; Le, Anh-Thu (My University, 2018)
We reexamine the recent pump-probe experiment with O2 using short intense infrared laser pulses theoretically. Using parameters that closely mimic the experimental conditions and taking into account the angle-dependent population redistribution due to resonant coupling between the relevant states, we show that the observed kinetic energy release spectra, including the energy-dependent structure and the quantum beat frequencies, can be accurately reproduced. Our results reveal additional important channels that were missed earlier. In particular, the strong contributions from O2+a4Πu and b4Σ−g states lead to the possibility of observing the interchannel beating. We further demonstrate that, by varying the laser parameters, the coherent nuclear wave-packet motions on different potential energy surfaces (PESs) can be probed and the properties of the PES can be examined. Future experiments with different wavelength lasers are proposed for better probing and controlling nuclear dynamics on different PESs.